Factors Influencing The Consumer Research Process: Market Target, Purchasing Behavior and Market Demand (Literature Review Of Consumer Behavior) - Toha, Mohamad; Supriyanto, Supriyanto (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2023)
Consumer research evolved as an extension of marketing research, focusing nearly entirely on consumer behavior rather than other components of the marketing process. The findings of consumer research are utilized to improve managerial decision-making. Marketers can forecast how consumers will react to promotional messaging and understand how they make purchasing decisions by studying their behavior. Consumers are currently blessed with a plethora of products to satisfy their demands. The era of producers controlling consumers has passed, and the era of consumers controlling producers has begun. Customers decide what products the company should make. Consumer behavior is defined as an activity or behavior, including the factors that influence the action, and is related to efforts to obtain items that suit their needs. Human behavior is so complicated that putting it into words is nearly impossible. The foundation of marketing management is consumer analysis. Marketing strategy and planning must be based on an understanding of the consumers who are the company's target market. This article examines the elements that drive the consumer research process, specifically the target market, purchasing behavior, and market demand, as well as a review of consumer behavior literature. The goal of this article is to develop a hypothesis on the influence of variables that will be used in future studies. This literature review article’s findings are as follows: 1) Target Market influences the Consumer Research Process; 2) Purchasing Behavior influences the Consumer Research Process; and 3) Market Demand influences the Consumer Research Process.